Development of a Hybrid Renewable Energy System with Co-Firing Option - Kirim, Yavuz; Sadikoglu, Hasan; Melikoglu, Mehmet (TAYLOR & FRANCIS INC, 2025)
In this study, a hybrid renewable energy systems (HRES) composed of solar photovoltaic and biogas co-firing is designed for a hazelnut cracking plant in Ordu province of Turkey. Technical and economic analysis are carried out based on the change in government incentives on renewable sources before (Option A) and after 2021 (Option B) based on net present cost (NPC) and cost of energy (COE). In addition, four different HRES configurations namely Scenarios 1, 2, 3, and 4 are analyzed to compare energy generation with/without co-firing of hazelnut shell and natural gas alongside with/without solar photovoltaic (PV). Sensitivity analysis is also made by considering grid sale capacity, inflation rate, discount rate, biomass price, and sellback rate. It is found that Option A has the lowest NPC and COE values, which are estimated as $3.000 M and $0.098/kW, respectively. In the sensitivity analysis of HRES configuration, total NPC and COE values between nominal discount rate and biomass price generally increase, while the values between expected inflation rate and sellback rate are on a downward trend. Consequently, Scenario-4 has the lowest NPC and COE values, and the highest renewable fraction at around 73.6%, whereas CO2 and NOx emissions are lowest in Scenario-2.
Keywords: Co-firing; hazelnut shell; hybrid energy system; net present cost; techno-economic analysis; GASIFICATION; GASIFIER; Energy & Fuels; Engineering; Environmental Sciences & Ecology